Pengaruh Free Cash Flow, Return on Assets, dan Cash Ratio Terhadap Kebijakan Dividen pada Perusahaan Manufaktur Subsektor Farmasi yang Terdaftar di Bursa Efek Indonesia pada Tahun (2020-2024) - Imelda Imelda; Wiwik Saraswati; Purwo Atmojo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Dividend policy plays a crucial role for issuers in balancing investor interests with the company's internal funding needs. The purpose of this study is to examine, analyze, and empirically prove the contribution of financial components, including Free Cash Flow, Return On Assets, and Cash Ratio, to dividend policy in pharmaceutical companies. A quantitative approach was selected for this study, utilizing secondary data in the form of annual financial statements accessed from the Indonesia Stock Exchange (IDX) during the 2020-2024 period. The results of this study indicate that in the simultaneous test (F-test), the variables of Free Cash Flow, profitability (Return On Assets), and liquidity (Cash Ratio) collectively exert a significant influence on the determination of dividend payment policy, with a significance value of 0.000. Partially (t-test), the analysis shows that the Free Cash Flow variable holds a dominant role and significantly affects dividend policy, confirming that the availability of residual operational cash flow serves as a strengthening foundation for management in allocating returns to investors while mitigating potential agency problems.